Thrips parvispinus Karny (Thysanoptera: Thripidae) pada Tanaman Cabai: Perbedaan Karakter Morfologi pada Tiga Ketinggian Tempat - Dewi Sartiami; Magdalena Magdalena; Ali Nurmansyah (Perhimpunan Entomologi Indonesia, 2011)
One of the important pests on chilli plants is Thrips parvispinus Karny (Thysanoptera: Thripidae). The presence of the pest is detected ranging from lowlands to highlands. This study was aimed to find out the morphological diversity of T. parvispinus at three different altitudes which include Cirebon (< 30 m asl), Bogor (300 - 400 m asl), and Cianjur (> 1200 m asl). At each level of altitude, it was collected 60 female adults of the thrips and then they were preserved into microscope preparations using Hoyer medium. The observed morphological characters of T. parvispinus were the length of body, the width of head, the width of thorax, the length of wing, and the color of body. The difference in morphological characters of the thrips in all three levels of altitude were analyzed using analysis of variance and Duncan's multiple range test. The correlation between altitude and body color was analyzed using chi- square test. Results showed that the body length, thoracic width, and wing length of the highland thrips were longer than those of the mid and lowland thrips. The three morphological characters showed significant differences between the mid and lowlands and the highlands, except for the character of head width. Changes in the color of the head, thorax, and abdomen were correlated to the level of the altitude.